Making Marks : An Exhibition of current Canadian Drawing. (Regina, Sask. : Norman Mackenzie Art Gallery, University of Regina, 1977)
Ballachey, Barbara ; Breeze, Claude ; Burton, Dennis ; Cameron, Alex ; Clarke-Darrah, Ann ; Craven, David ; Deacon, Peter ; Detheridge, Allan ; Dubé, Chantal ; Evans, Robert T. ; Fiore, Giuseppe ; Frick, Joan ; Gillies, Jim ; Graham, K.M. ; Grauer, Sherry ; Harris, Salmon ; etc.
Making Marks : An Exhibition of current Canadian Drawing, Norman Mackenzie Art Gallery, University of Regina, Regina, September 2 to October 2, 1977
boek
Keywords: Canada